Stimulation of the mouse rRNA gene promoter by a distal spacer promoter. - Paalman, M H (1995)
We show that the mouse ribosomal DNA (rDNA) spacer promoter acts in vivo to stimulate transcription from a downstream rRNA gene promoter. This augmentation of mammalian RNA polymerase I transcription is observed in transient-transfection experiments with three different rodent cell lines, under noncompetitive as well as competitive transcription conditions, over a wide range of template concentrations, whether or not the enhancer repeats alone stimulate or repress expression from the downstream gene promoter. Stimulation of gene promoter transcription by the spacer promoter requires the rDNA enhancer sequences to be present between the spacer promoter and gene promoter and to be oriented as in native rDNA. Stimulation also requires that the spacer promoter be oriented toward the enhancer and gene promoter. However, stimulation does not correlate with transcription from the spacer promoter because the level of stimulation is not altered by either insertion of a functional mouse RNA polymerase I transcriptional terminator between the spacer promoter and enhancer or replacement with a much more active heterologous polymerase I promoter. Further analysis with a series of mutated spacer promoters indicates that the stimulatory activity does not reside in the major promoter domains but requires the central region of the promoter that has been correlated with enhancer responsiveness in vivo.